2013
DOI: 10.1111/jnc.12258
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the K+‐Cl co‐transporter KCC2 in the sensitization to morphine‐induced hyperlocomotion under chronic treatment with zolpidem in the mesolimbic system

Abstract: Benzodiazepines are commonly used as sedatives, sleeping aids, and anti-anxiety drugs. However, chronic treatment with benzodiazepines is known to induce dependence, which is considered related to neuroplastic changes in the mesolimbic system. This study investigated the involvement of K + -Cl À cotransporter 2 (KCC2) in the sensitization to morphine-induced hyperlocomotion after chronic treatment with zolpidem [a selective agonist of c-aminobutyric acid A-type receptor (GABA A R) a1 subunit]. In this study, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…It has been reported that zolpidem suppresses the lomotor activity in mice (Heldt and Ressler, 2010). Furthermore, we suggested that single administration of zolpidem did not affect morphine-induced hyperlocomotion (Shibasaki et al, 2013a). Taken together, it is important that chronic treatment with zolpidem enhanced the morphine-induced hyperlocomotion via up-regulation of mGlu 5 receptor.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…It has been reported that zolpidem suppresses the lomotor activity in mice (Heldt and Ressler, 2010). Furthermore, we suggested that single administration of zolpidem did not affect morphine-induced hyperlocomotion (Shibasaki et al, 2013a). Taken together, it is important that chronic treatment with zolpidem enhanced the morphine-induced hyperlocomotion via up-regulation of mGlu 5 receptor.…”
Section: Discussionmentioning
confidence: 90%
“…The locomotor activity of mice was measured by an ambulometer (ANB-M20, O'Hara, Co., Ltd., Tokyo, Japan) as described previously (Shibasaki et al, 2013a). Briefly, a male ICR mouse was placed in a tilting-type round activity cage of 20 cm in diameter and 19 cm in height.…”
Section: Locomotor Activitymentioning
confidence: 99%
See 3 more Smart Citations